A flavonoid-rich fraction of Euphorbia peplus attenuates hyperglycemia, insulin resistance, and oxidative stress in a type 2 diabetes rat model - Alruhaimi, Reem S.; Mostafa-Hedeab, Gomaa; Abduh, Maisa Siddiq; Bin-Ammar, Albandari; Hassanein, Emad H. M.; Kamel, Emadeldin M.; Mahmoud, Ayman M. (Frontiers in Pharmacology, 2023)
Background: Type 2 diabetes (T2D) is a metabolic disorder characterized by insulin resistance (IR) and hyperglycemia. Plants are valuable sources of therapeutic agents for the management of T2D. Euphorbia peplus has a wide traditional medicinal use, but its beneficial role in T2D was not investigated. Methods: The anti-diabetic efficacy of E. peplus extract (EPE) in rats with T2D induced by high-fat diet and streptozotocin was studied. Diabetic rats received 100, 200 and 400 mg/kg EPE for 4 weeks. Results: Phytochemical fractionation of the aerial parts of E. peplus led to the isolation of seven known flavonoids. Rats with T2D exhibited IR, impaired glucose tolerance, decreased liver hexokinase and glycogen, and upregulated glycogen phosphorylase, G6Pase, and F-1,6-BPase. Treatment with 100, 200, and 400 mg/kg EPE for 4 weeks ameliorated hyperglycemia, IR, liver glycogen, and the activities of carbohydrate-metabolizing enzymes. EPE attenuated dyslipidemia, serum transaminases, TNF-α, and IL-1β and liver lipid accumulation, NF-κB p65, lipid peroxidation and nitric oxide, and enhanced antioxidants. All EPE doses upregulated serum adiponectin and liver PPARγ in HFD/STZ-induced rats. The isolated flavonoids showed in silico binding affinity toward hexokinase, NF-κB, and PPARγ. Conclusion: E. peplus is rich in flavonoids and its extract ameliorated IR, hyperglycemia, dyslipidemia, inflammation and redox imbalance, and upregulated adiponectin and PPAR in rats with T2D.